2011
DOI: 10.3109/10428194.2011.580026
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic relevance of tumor associated macrophages in advanced stage classical Hodgkin lymphoma

Abstract: Although the treatment of Hodgkin lymphoma (HL) has been improved, distinguishing reliable prognostic biomarkers could better stratify patients for more effective treatment. We analyzed the prognostic relevance of CD68+ tumor-associated macrophages (TAMs) by immunohistochemical analysis at diagnosis and standard clinical parameters in 52 ABVD (doxorubicin, bleomycin, vinblastine, dacarbazine)-treated patients with advanced stage classical HL (cHL). Patients with >25% CD68+ TAMs compared to those with ≤25% had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 42 publications
1
41
0
1
Order By: Relevance
“…However, different studies reported different association of high CD68 with some clinicopathological findings as B symptoms, [38,41,42] age, [35,41] mixed cellularity subtype, [5,35,[41][42][43] primary treatment failure, [5,19,36,38] male sex, [35] bulky disease, [35] and IPS. [35,37,41] In our study, there was association between high CD68+ TAM infiltration and higher disease stage similar to previous reports. [19,35,42,44] In the present study, we demonstrated a positive correlation between high CD68+ TAM infiltration and shortened DFS but not DSS.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, different studies reported different association of high CD68 with some clinicopathological findings as B symptoms, [38,41,42] age, [35,41] mixed cellularity subtype, [5,35,[41][42][43] primary treatment failure, [5,19,36,38] male sex, [35] bulky disease, [35] and IPS. [35,37,41] In our study, there was association between high CD68+ TAM infiltration and higher disease stage similar to previous reports. [19,35,42,44] In the present study, we demonstrated a positive correlation between high CD68+ TAM infiltration and shortened DFS but not DSS.…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings were reported in previous studies. [16,[37][38][39][40] Also high CD68 was not found to be independent predictor of primary treatment outcome. However, different studies reported different association of high CD68 with some clinicopathological findings as B symptoms, [38,41,42] age, [35,41] mixed cellularity subtype, [5,35,[41][42][43] primary treatment failure, [5,19,36,38] male sex, [35] bulky disease, [35] and IPS.…”
Section: Discussionmentioning
confidence: 96%
“…Pathologically, cHL is characterized by the presence of a small number of diagnostic Reed-Sternberg cells in a background of bystander reactive cells composed of lym-vestigators, including the present authors, validated the adverse prognostic impact of a high TAM content using immunohistochemical staining for CD68 and CD163 [5][6][7][8][9][10]. TAMs are believed to provide trophic factors that directly accelerate the growth and survival of malignant lymphocytes [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…69,70 Indeed, overexpression of macrophage antigens in tumor tissue may indicate a prometastatic state and may be associated with poor prognosis. 71,72 The molecular mechanisms leading to the expression of immune antigens by tumor cells remain still incompletely understood. The intercellular genetic exchange through cell fusion or release of exosomes may have a role in induction of immune markers in cancer cells.…”
Section: Cd68 In Cancermentioning
confidence: 99%